2001
DOI: 10.3171/jns.2001.94.1.0043
|View full text |Cite
|
Sign up to set email alerts
|

Pallidotomy for Parkinson disease: a review of contemporary literature

Abstract: Unilateral pallidotomy is effective and relatively safe in the treatment of PD; however, limited data are available on the long-term outcome of this procedure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
53
1
6

Year Published

2001
2001
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 124 publications
(63 citation statements)
references
References 84 publications
3
53
1
6
Order By: Relevance
“…Horak and Anderson (1984) and Mink and Thatch (1993) observed that monkeys with lesions causing increased activity within the GPi exhibited significant motor slowing. The therapeutic effects of surgical disruption of the output of the GPi in Parkinson disease are also consistent with this model (Pfann et al, 1998;Alkhani and Lozano, 2001;Lozano and Lang, 2001;Dostrovsky et al, 2002).…”
Section: Neuroanatomy and Chemistry Of The Subcortical Motor Systemsupporting
confidence: 65%
“…Horak and Anderson (1984) and Mink and Thatch (1993) observed that monkeys with lesions causing increased activity within the GPi exhibited significant motor slowing. The therapeutic effects of surgical disruption of the output of the GPi in Parkinson disease are also consistent with this model (Pfann et al, 1998;Alkhani and Lozano, 2001;Lozano and Lang, 2001;Dostrovsky et al, 2002).…”
Section: Neuroanatomy and Chemistry Of The Subcortical Motor Systemsupporting
confidence: 65%
“…The risk of haemorrhagic complication is higher when using MER, which was confi rmed by studies (10,8), where there was a signifi cantly higher incidence of haemorrhage in centres using microelectrodes compared to the centres, which did not use them. Other studies found 4-5 times higher risk of haemorrhage with using MER (16).…”
Section: Discussionsupporting
confidence: 57%
“…The incidence of haemorrhagic complications is found in literature in the review studies (10,11) as well as in studies with a higher number of patients (12,13,7,14). The average incidence of haemorrhagic complications is 5 %, asymptomatic in 1.9 %, symptomatic in 2.1 % and resulting in permanent defi cit or death in 1 %.…”
Section: Discussionmentioning
confidence: 81%
“…In the latter, the following were found: dysarthria (3.6%), visual field defect (2.4%), facial weakness (2.4%), hypophonia (1.2%), dysphagia (2.4%), personality changes (3.9%), and hypersalivation (2.1%). In most instances, the rates from the prospective series are higher than those shown by the Alkhani and Lozano 57 analysis. The effects of technical issues on complications were assessed with respect to the use of microelectrode mapping, but the effect of location along the learning curve could not be assessed by either study.…”
Section: Is Posteroventral Pallidotomy a Safe Therapy For Pd?mentioning
confidence: 68%
“…How often and how severe are the adverse effects from pallidotomy, and how do they compare to DBS? From a literature survey covering 1510 patients, Alkhani and Lozano 57 found a rate of persistent (Ͼ3 months) adverse effects of 14.3%, including symptomatic infarction or hemorrhage (1.7%), dysarthria (1.6%), visual field defect (1.5%), facial weakness (1.3%), hypophonia (1.3%), and dysphagia (0.5%). These rates may be confounded by being derived mostly from retrospective data sets, and representing centers with varying technical proficiency with the operation, which may have counteracting effects.…”
Section: Is Posteroventral Pallidotomy a Safe Therapy For Pd?mentioning
confidence: 99%